Analisa Faktor Waktu Pulih Sadar Pasien Post Laparatomi Anestesi Umum - Risdayati Risdayati; Fitrian Rayasari; Siti Badriah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to analyze the dominant factors associated with the time to recover consciousness of patients with laparotomy, general anesthesia in the Recovery Room of Bhayangkara Hospital Tk I Jakarta. The research method used is analytical research with a cross-sectional approach. The results showed a relationship between age and recovery time after general anesthesia post-laparotomy (p = 0.028). There was a difference between the sexes and the time to recover consciousness of the laparotomy patients with general anesthesia (p = 0.04). There was a difference between ASA and recovery time of conscious laparotomy patients with general anesthesia (p = 0.01). There was a correlation between BMI and awake in patients with available anesthesia laparotomy (p = 0.0005). There was no relationship between body temperature, fasting time, and duration of operation with p values (0.59, 0.6, and 0.94), respectively. In conclusion, the dominant factor that affects the recovery time of consciousness in post-laparotomy general anesthesia patients is body temperature, namely hypothermia. Keywords: Anesthesia, Laparotomy, Conscious Recovery, Thermoregulation